Annals of Indian psychiatry official publication of Indian Psychiatric Society-Western Zonal Branch.
Annals of Indian Psychiatry, a publication of Indian Psychiatric Society - Western Zonal Branch, is a peer-reviewed print + online Semiannual journal. The journal's full text is available online at http://www.anip.co.in. The journal allows free access (Open Access) to its contents and permits authors to self-archive final accepted version of the articles on any OAI-compliant institutional / subject-based repository.